Mechanisms of normal reflection at metal interfaces: III Международный семинар по микроконтактной спектроскопии Харьков, Украина, 8–11 сентября 2014 г. - Gloos, K.; Tuuli, E. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
Andreev-reflection spectroscopy of elemental superconductors in contact with nonmagnetic normal metalsreveals that the strength of normal-reflection varies only slightly. This observation imposes strong constrictionson the three possible normal-reflection mechanisms: tunneling through a dielectric barrier, reflection due to the different electronic properties of the two electrodes, and diffusive transport caused by elastic scattering in the contact region. We discuss in detail the role played by Fermi-surface mismatch, represented by the differentFermi velocities on both sides of the contact interface. We find that it is at least not the dominant mechanism andpossibly completely absent in the Andreev-reflection process.